Modifikasi Sistem Buka-Tutup Dan Struktur Tulangan Kap Mesin Purwarupa Kendaraan Listrik - Pandoe Pandoe; Antonius Adi Soetopo; Rifki Tri Pangestu (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The engine hood of the prototype electric vehicle, developed in a previous study, still uses a permanent mounting system, which limits access for inspection and maintenance of the vehicle’s front compartment. This study aims to implement an opening-closing system and a reinforcement structure for the hood using 1 mm-thick Steel Plate Cold Commercial (SPCC). The research was conducted through the following stages: design using SolidWorks 2022; fabrication of the hood panel and reinforcement structure; assembly of the opening-closing mechanism components; and evaluation of the implementation results. The opening-closing mechanism consists of a hood hinge, a hood latch, and a hood support rod, while the reinforcement structure was fabricated using a 25 × 25 × 2 mm hollow square profile. The results of the study indicate that the opening-closing system and the reinforcement structure were successfully implemented according to the design, forming a single structural unit with the hood panel. The reinforcement structure serves to strengthen the panel while also acting as a mounting bracket for the hood hinge and hood latch, whereas the implementation of the opening-closing system improves ease of access to the vehicle’s front compartment for inspection and maintenance compared to the previous design, which used a permanent mounting system. Furthermore, the development of the hood enhances functionality without altering the primary dimensions or the basic concept of the front body of the prototype car.